Effect of Metabolic Syndrome on the Mobility Benefit of a Structured Physical Activity Intervention—The Lifestyle Interventions and Independence for Elders Randomized Clinical Trial. Issue 6 (28th March 2017) - Botoseneanu, Anda; Chen, Haiying; Ambrosius, Walter T.; Allore, Heather G.; Anton, Stephen; Folta, Sara C.; King, Abby C.; Nicklas, Barbara J.; Spring, Bonnie J.; Strotmeyer, Elsa S.; Gill, Thomas M.
Abstract : Objectives: To test whether structured physical activity (PA) is associated with a greater reduction in major mobility disability (MMD) in older persons with metabolic syndrome (MetS) than in those without. Design: Data from the Lifestyle Interventions and Independence for Elders (LIFE) Study, a multicenter randomized trial of 1, 635 persons with assessments every 6 months (average 2.7 years). Setting: Eight U.S. centers. Participants: Sedentary men and women aged 70 to 89 with functional limitations (N = 1, 535); 100 participants were excluded because of missing MetS data. Intervention: Participants were randomized to a moderate‐intensity PA program (n = 766) or a health education program (n = 769). Measurements: MetS was defined according to the 2009 multiagency harmonized criteria. Outcomes included incident MMD (loss of ability to walk 400 m) and persistent MMD (two consecutive MMD diagnoses or one MMD diagnosis followed by death). Results: Seven hundred sixty‐three (49.7%) participants met criteria for MetS. PA reduced incident MMD more than health education did in participants with MetS (hazard ratio (HR) = 0.72, 95% confidence interval (CI) = 0.57–0.91, P = .007) but not in those without MetS (HR = 0.96, 95% CI = 0.73–1.25, P = .75); the test for statistical interaction was not significant ( P = .13). PA reduced the risk of persistent MMD in participants with MetS (HR = 0.57, 95% CI = 0.41–0.79, P < .001) but not in those without MetS (HR = 0.97, 95% CI = 0.67–1.41, P = .87). The test for statistical interaction was significant ( P = .04). Conclusion: Moderate‐intensity PA substantially reduces the risk of persistent MMD in older persons with functional limitations with MetS but not in those without MetS. Comparable results were observed for incident MMD. The LIFE PA program may be an effective strategy for reducing mobility disability in vulnerable older persons with MetS.